2013
DOI: 10.1016/j.diagmicrobio.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Single-tier testing with the C6 peptide ELISA kit compared with two-tier testing for Lyme disease

Abstract: Background The two-tier serologic testing protocol for Lyme disease has a number of shortcomings including low sensitivity in early disease; increased cost, time and labor; and subjectivity in the interpretation of immunoblots. Methods The diagnostic accuracy of a single-tier commercial C6 ELISA kit was compared with two-tier testing. Results The C6 ELISA was significantly more sensitive than two-tier testing with sensitivities of 66.5% (95% C.I.:61.7-71.1) and 35.2% (95%C.I.:30.6-40.1), respectively (p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 41 publications
4
119
1
4
Order By: Relevance
“…However, our study was inadequately powered to show a sensitivity benefit of the C6 EIA in early Lyme disease, because only 14% of the serum samples from patients with Lyme disease came from those with solitary EM lesions. In keeping with findings from previous studies [4,7,9,16], we found that the C6 EIA alone was less specific than standard 2-tiered testing. The specificity of a 2-tiered strategy with C6 EIA followed by supplemental immunoblot did not differ from that of standard WCS EIA based 2-tiered testing.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, our study was inadequately powered to show a sensitivity benefit of the C6 EIA in early Lyme disease, because only 14% of the serum samples from patients with Lyme disease came from those with solitary EM lesions. In keeping with findings from previous studies [4,7,9,16], we found that the C6 EIA alone was less specific than standard 2-tiered testing. The specificity of a 2-tiered strategy with C6 EIA followed by supplemental immunoblot did not differ from that of standard WCS EIA based 2-tiered testing.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have evaluated the performance of the C6 EIA in adults [4,8,9,14,15]. In the largest study to date, the C6 EIA was evaluated as a stand-alone test in serum samples from 528 well-characterized patients with Lyme disease as well as from healthy blood donors [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations